All in a day's work to build single mum a home - UMP, . (Penerbit, Berita Harian Sdn. Bhd., 2015)
Kuala Lipis: After living in a tent and garage for more than three weeks, 46-years-old Zalmah Sani and her six children can now heave a sigh of relief as a team of volunteers from Universiti Malaysia Pahang (UMP) built a temporary home for them at Kampung Aur Gading here in just a single day